Slavery in the 18th–19th Century United States in Julian Ursyn Niemcewicz’s Relations from Travels through America - Kaniecka, Monika (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
Julian Ursyn Niemcewicz, Polish writer and politician, in 1797–1807 travelled to the United States twice. During that time he wrote a few comprehensive journals, which described his experiences, observations and opinions about that country. Niemcewicz, while visiting the USA, was delighted about the state, that reminded him the ideals of equality and freedom. However, during the journey he encountered the issue of slavery. During the stay in Virginia – the only south state he visited – Niemcewicz described in details the living conditions of slaves and the way they were treated by their owners. Moreover, he tried to study the possible causes of slavery in the southern parts of the USA. The aim of the article is to analyze the way Niemcewicz perceived slavery, in which way this views reflected the context of epoque and how the existence of slavery influenced his vision of America.